2019
DOI: 10.1080/09546553.2019.1608951
|View full text |Cite
|
Sign up to set email alerts
|

Does Terrorism Dominate Citizens’ Hearts or Minds? The Relationship between Fear of Terrorism and Trust in Government

Abstract: Terrorism only poses a small risk to people but tends to be a major source of public fear. Through fear, terrorism has far-reaching implications for public governance. In this paper we look at trust in government as a potential mitigating factor of fear of terrorism. We discern between calculative trust, based on analytical assessment of previous and expected future actions, and relational trust, based on emotions and perceived value similarity with government. We find that relational trust decreases fear of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The acts have not disrupted the social fabric of societies by instilling distrust between people or caused them to question the basic assumptions on which everyday activities are built (Maras, 2013; see also Muro, 2019). In other words, people have sustained their sense that experts and administrations are capable of identifying and managing the respective threats as well as organising effective responses to attacks (cf., Van Der Does et al, 2019). The knowledge strategy for maintaining the continuity and enhancing the security ex post facto of a CI has convinced the people of its capability and proven its reliability quite well (Hoffman and Shelby, 2017).…”
Section: Terrorism Targeted At Critical Infrastructuresmentioning
confidence: 99%
“…The acts have not disrupted the social fabric of societies by instilling distrust between people or caused them to question the basic assumptions on which everyday activities are built (Maras, 2013; see also Muro, 2019). In other words, people have sustained their sense that experts and administrations are capable of identifying and managing the respective threats as well as organising effective responses to attacks (cf., Van Der Does et al, 2019). The knowledge strategy for maintaining the continuity and enhancing the security ex post facto of a CI has convinced the people of its capability and proven its reliability quite well (Hoffman and Shelby, 2017).…”
Section: Terrorism Targeted At Critical Infrastructuresmentioning
confidence: 99%
“…We conducted two waves of a 'fear of terrorism' survey in the period 6-28 November 2017 (Van der Does et al, 2021) and 4 In the taxonomy created by Gabriel and Greve (2003, pp. 608-609), the direct usage of 'fear' in the survey questions refers to the so-called global measurement of fear of crime and responding to such a global fear question is an especially difficult cognitive task.…”
Section: Data and Operationalizationmentioning
confidence: 99%
“…We conducted two waves of a ‘fear of terrorism’ survey in the period 6–28 November 2017 (Van der Does et al, 2021) and 4–26 May 2020, respectively. The second wave included the same questions as the prior survey, but it also contained questions related to the COVID‐19 pandemic.…”
Section: Introduction: a Shift In Fear Of Terrorism?mentioning
confidence: 99%
“…One effect of this could be the erosion of trust in security institutions. For example, a successful attack with an impactful weapon might harm the reputation of intelligence institutions, law enforcement, and the military since it may result in the public ceasing to trust them and their ability to keep society safe [50], p. 214; [65], p. 11. 5 (2) Economic loss and (at least temporary) displacement could add to the impact of a terrorist attack.…”
Section: The Terrorist Weapon Rating Systemmentioning
confidence: 99%
“…This effect is known as the rally effect. However, recent studies showed that this effect is only a short term effect in the immediate aftermath of an attack[20,32,65].…”
mentioning
confidence: 99%